Press & media coverage - Bohari, Mohamad Musa; Chik, Yahutazi; Kamaruddin, Siti Faridah; Long, Suffina; Juhari, Nur Nadia Qausar; Joseph, Stefanie Natasha Rich (Corporate Communication Unit, UiTM Mukah Campus, 2023)
The achievement of UiTM Sarawak Kampus Mukah branch featured in the press & media coverage reflects the institution's excellence in academics, innovation, and community engagement. This media recognition strengthens the campus's role as a key driver of educational development in central Sarawak and enhances UiTM'S national reputation.